Shaking-Swing Coupled Vibration Analysis of a Laminar Composite Rotating Blade by the Finite Element Method - Yao, X.; Zheng, C. (Проблемы прочности, 2015)
For studying the vibration characteristics of a laminar composite rotating blade, the spin softening effect calculated by the finite element method (FEM) was incorporated with the prestress effect to analyze shaking, swing, torsion, and coupled vibrations. The mathematical formula was derived. The study shows that the centrifugal force exerts influence on the difference in vibration frequencies. The laminar composite can reduce an influence of the spin softening on the first swing vibration frequency because of its structure and smaller density. With the variation of rotating velocity, the blade spin softening can lead to the coupled first shaking and first swing vibrations. In the coupled vibrations, swing is contained in the shaking mode and shaking is also contained in the swing one, which is the reason of major blade damages. The results confirm the complexity of the dynamic characteristics of the laminar composite rotating blade. This method is also well applicable to the dynamic design of such blades. Для исследования вибрационных характеристик вращающейся лопатки из слоистого композиционного материала эффект ротационного разупрочнения, рассчитанный методом конечных элементов, в сочетании с эффектом предварительного напряжения были использованы для анализа тряски, качания, кручения и комбинированных колебаний. Была выведена математическая формула. Исследование показывает, что центробежная сила оказывает влияние на различия в частоте колебаний. Благодаря своей структуре и меньшей плотности слоистый композиционный материал позволяет уменьшить влияние ротационного разупрочнения на первую частоту качания. При изменении скорости вращения ротационное разупрочнение лопатки может приводить к совместным тряске и качанию на первой частоте. При совместных колебаниях качание присутствует в моде тряски, а тряска в моде качания, что является причиной серьезных повреждений лопатки. Результаты подтверждают сложность динамических характеристик вращающейся лопатки из слоистого композиционного материала. Этот метод также дает хорошие результаты при динамическом проектировании таких лопаток.